Application of HPTLC and HPLC for purification of bioactive compounds from plant extract for gout remedy - Jamal, Parveen; Azmi, Saiful Mohammad Nizam; Amid, Azura (IIUM Press, 2016)
Plants and natural products have since time immemorial contributed significantly to the general well being of mankind (Bhat et al., 2008). Commanding the belief of as high as 80% of the population in developing countries, plants have been prescribed for treating many diseases through traditional and complementary medicines. The impressive track record that plants have in directly or indirectly providing new drugs for therapeutic uses and the rising costs of medical treatments are believed to have contributed to the continuing belief on the efficacy of herbal medicines. The Malaysian market for dietary supplements, nutraceuticals and herbal medicines has been estimated to be about US$526 million, much of which are made up of imported products. Bioactive compounds from plants (inhibitors) could block the biosynthesis of uric acid from purine in the body, which should be one of the therapeutic approaches for treating hyperuricemia. There are numerous studies on bioactive inhibitors (xanthine oxidase inhibitors -XOI) using medicinal plants as their raw materials. Different extraction system, solvent and process conditions have been used to extract the desired compounds from plants.